Israeli Parents' Lived Experiences of Music Therapy With Their Preterm Infants Post-Hospitalization. (5th June 2022) - Epstein, Shulamit; Elefant, Cochavit; Ghetti, Claire
Abstract: In the current study, we aimed to explore the lived experience of Israeli parents who engaged in musical dialogues with their preterm infants during music therapy (MT) after being discharged from the neonatal intensive care unit (NICU), as a part of the multinational LongSTEP RCT. Seven participants of the main trial were invited to engage in semi-structured in-depth interviews intertwining listening to audio recordings from their music therapy sessions in an adapted interpersonal process recall (IPR) procedure. The interviews were transcribed and analyzed using interpretative phenomenological analysis (IPA). We understood the participants' experiences to reflect two main themes: 1) Music therapy as a potential means of transformation in communication skills, resourcefulness and sense of agency; and 2) emotional and musical preconditions for parental engagement in MT. The findings illustrate how a specific group of Israeli parents experienced MT as offering them a means of expanding their relationship with their preterm infants after discharge. Based on our findings, we recommend that music therapists consider parents' musical and emotional resources during post-discharge MT to meet the individual needs of families.